2019
DOI: 10.1002/adma.201903909
|View full text |Cite
|
Sign up to set email alerts
|

Layered Structure Causes Bulk NiFe Layered Double Hydroxide Unstable in Alkaline Oxygen Evolution Reaction

Abstract: in alkaline media. The surprisingly low OER overpotential of NiFe LDH has triggered a great deal of research attentions to reveal the reaction mechanism. [4,5] Besides, lots of work have been done to further reducing the overpotential of NiFe LDH, for example, via incorporation of a third metal, [6][7][8] hybridization with carbon materials, [9,10] and applying NiFe selenide as the templating precursor. [11] Although great attention has been paid to improve the OER activity and investigate the active site of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(263 citation statements)
references
References 24 publications
3
257
0
3
Order By: Relevance
“…A study led by the Liu group found that the layered structures in NiFe-based electrocatalysts could limit the diffusion of proton acceptors (e.g., OH − ) into the small interlayer spaces in the materials during OER. [129] Furthermore, they indicated that the local acidic environment would cause cation dissolution, making the electrocatalyst unstable. This work provided an important explanation as to why some previously reported, highly active NiFe-based OER electrocatalysts usually had very limited catalytic lifetimes (<100 h).…”
Section: Porous Nife-based Electrocatalysts For Alkaline Oermentioning
confidence: 99%
“…A study led by the Liu group found that the layered structures in NiFe-based electrocatalysts could limit the diffusion of proton acceptors (e.g., OH − ) into the small interlayer spaces in the materials during OER. [129] Furthermore, they indicated that the local acidic environment would cause cation dissolution, making the electrocatalyst unstable. This work provided an important explanation as to why some previously reported, highly active NiFe-based OER electrocatalysts usually had very limited catalytic lifetimes (<100 h).…”
Section: Porous Nife-based Electrocatalysts For Alkaline Oermentioning
confidence: 99%
“…[81,82] The interlayer basal plane in a bulk NiFe-LDH has been reported to be conducive to the OER activity, and the tardy diffusion of proton acceptors (e.g., OH − ) within the NiFe-LDH interlayers during OER causes the NiFe-LDH to dissolve, thereby decreasing the OER activity over time. [83] To expose additional active sites and improve the NiFe-LDH stability, various valid methods have been explored for preparing ultrathin nanometer-scale sheets. For example, Gao and Yan synthesized single-unit-cell-thick (≈1.3 nm) and defect-rich NiFe-LDH nanosheets (NSs) in a simple manner ( Figure 3a); these NSs exhibited Tafel a slope of 33.4 mV dec −1 and an almost 100% faradaic efficiency.…”
Section: The Nife-layered Hydroxide (Nife-ldh) Familymentioning
confidence: 99%
“…It is because the slow diffusionofa lkaline electrolyte into NiCu DHs interlayers are easily induce al ocal acidic environment, thus leading to the dissolution of hydroxyl groups and causing structural destruction. [14] Accordingly,a iming at boosting the conversion efficiency of ÀOH to ÀOOH and enhancing the electrochemical corrosion resistance, how to designt he distribution and retain availability of hydroxyl species in NiCu DHs becomes ac ritical problem. [15] Herein, we report the systematic synthesis of NiCu DHs with tunable intercalations and morphologies [nanotyres (T), nanoflowers (F), and nanonets (N)] through ao ne-step solvothermal approacha nd investigate their structure-function relationship towardsa lkaline AOR.…”
Section: àmentioning
confidence: 99%